IMPACT OF HOME EXERCISING ON PHYSICAL, HEALTH AND PSYCHOLOGICAL ASPECTS, IN TIME OF CORONA VIRUS (COVID 19) PANDEMIC. - Ben Smisha,; Guezgouz Mohamed,; Mokrani Djamel, (Sport Scientific And Practical Aspects, 2025)
The study aimed to identify the positive role of home exercise in helping a person to adhere to home quarantine through practice, and to what extent is it reflected on the aspects (physical, health, and psychological), in light of the Corona pandemic. The researcher used the descriptive analytic approach in the study, and the studied community is represented by 725 members of the local community of citizens residing in Algeria, quarantined in homes, and aged between (15 and more than 65 years), using an electronic questionnaire form, published on social media. The study showed that the degree of level of trends in the study sample regarding the effect of home exercise on aspects (physical, health and psychological) was high. As well as the availability of sports tools, and the use of social media, help in the physical health and psychological aspects of quarantined people, in addition to helping them better accept to stay at home.